ANALYSIS OF VIBRATIONS OF FURNACE BARS ON THE ELASTIC SUPPORT OF THE CLEANER OF FIBROUS MATERIALS (Scientific journal of the Fergana State University, 2023)
The article presents a new effective structural scheme of the principle of operation of the purifier of fibrous material from large impurities. On the basis of theoretical studies, the patterns of oscillatory motion and the graphic dependences of the parameters of the grate of the cleaner are determined. The analysis determined the recommended values of the parameters of the grate.